Analisis Yuridis Pembuktian Sengketa Transfer Pricing - Arrisman, Arrisman; Fauzi, Ahmad (Syntax Literate, 2025)
This research is about the juridical analysis of the proof of transfer pricing disputes with an example of the case of the Tax Court decision No.Put.74576/PP/M.IB/15/2016. The ruling granted an appeal filed by PT HI, a foreign investment company from Japan. Transfer Pricing or TP occurs in transactions involving "Taxpayers with parties who have a special relationship" (affiliates) based on Article 18 of the Income Tax Law. Taxpayers with affiliated transactions are required to fill in the information and method of testing TP on the Corporate Income Tax Return based on TP documentation. In the case of PT HI, the Director General of Taxes checks import purchase transactions from affiliates using the method listed in the Corporate Income Tax Return of PT HI. PT HI fills in the information of affiliate transactions in the Corporate Income Tax Return not based on TP documentation. PT HI makes TP documentation, and submits it to the tax office during the objection process. At the objection stage, the DGT rejected the objection submitted by PT HI. PT HI then appealed to the Tax Court. In its decision, the Tax Court granted the appeal and canceled the DGT's correction to the import purchase cost. This study aims to find out and analyze the efforts of the Panel of Judges at the Tax Court to obtain material truth in making decisions by referring to the theory of free proof. This study uses a normative juridical research method because it focuses on literature research which essentially examines legal principles, legal systematics, and legal synchronization by analyzing them. The results of the study show that the Tax Court with the principle of free proof obtains material truth by digging up legal facts from affiliate transactions.